Kecerdasan Emosi, Persepsi terhadap Pendidikan Karakter Cinta Damai dan Penyesuaian Diri Remaja - Bachri, Sjaiful; Suharnan, Suharnan (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. The purpose of this study to examine the relationship of emotional intelligence and perception of the peace-loving character education to adolescent adjustment. The subjects of this study were 150 high school students in the country I Ketapang Sampang. Data collected melui scale of emotional intelligence, perception and character education peaceful adjustment. Data analysis using regression and correlation techniques. The results of the study show that there is no correlation between emotional intelligence and adolescent adjustment. However, different results indicated that there is significant and positive relationship between perceptions of peace-loving character education with adolescent adjustment.Keywords : Emotional Intelligence, Perception of Peace-Loving Character Education, Adolescent Adjustment.